Notes on the Representation of the Heritage Landscape - Mercedes Linares Gómez del Pulgar (Diségno)
In the last three decades, a wide panorama of publications, theories and definitions on the landscape and its representation has opened up before us. In this brief text I will only try to offer, with the help of a few outstanding authors, some notes on the cultural reasons for a historical need that crystallized in the 17th century with the awareness of the landscape and the beginning of modern science, and that, four centuries later, has led to a concern on a universal scale: a new awareness of the loss of quality of the landscapes of cultural heritage. The optimism of those ‘infinite works of nature’ that Leonardo da Vinci wrote down in his notebooks seems very far away. [read more]